Development and Evaluation of Effervescent Powder Formulations Combining Red Ginger Extract and Honey - Azahra, Astrid Sulistya; Prabowo, Agung; Yasmin, Arla Aglia (Corespub, 2024)
Effervescent powder formulations combining red ginger (Zingiber officinale var. rubrum) extract and honey were developed and evaluated for their physical, chemical, and antibacterial properties. The formulations were prepared using wet granulation method, and their organoleptic properties, moisture content, flow characteristics, dispersibility, foam height, pH, and hedonic responses were assessed. Additionally, the antibacterial activity of the formulations against Streptococcus pyogenes was evaluated using agar diffusion method. The results showed that the formulations exhibited variations in color, odor, taste, and physical form, with formulation F3 containing 10% red ginger extract demonstrating the best sensory attributes. All formulations met the moisture content and flow time criteria, indicating good stability and handling properties. They also displayed rapid dispersibility and proper foam height upon dissolution. The pH values fell within the acceptable range for consumption. However, none of the formulations showed significant antibacterial activity against Streptococcus pyogenes. Further optimization may be required to enhance the formulations' antibacterial efficacy.